2012
DOI: 10.1590/s0103-863x2012000300004
|View full text |Cite
|
Sign up to set email alerts
|

Relacionamentos de amizade íntima entre jovens adultos

Abstract: Abstract:The literature is consensual regarding the importance of friendships throughout the lifespan; most of the time for improvements in the quality of life. The aim of this study was to investigate and describe intimate friendship relationships among young adults. Participants were 98 young adults aged between 18 and 30. Sampling procedures were based on the Respondent Driven Sampling technique. The instrument was composed of three self-report questionnaires and data were analyzed quantitatively. Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
(35 reference statements)
0
3
0
5
Order By: Relevance
“…However, they also found that such homogeneity does not take place so comprehensively, there are aspects that would escape this tendency, such as religion. 6 Authors 19 evaluated the effect of diversity attributes in the university environment, in interpersonal relationships and in the academic performance of a private superior teaching institution. Most of the students consider it important to have common values in education and training, interest in studying, habits and leisure in the students' approach and in the formation of social groups and in the classroom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they also found that such homogeneity does not take place so comprehensively, there are aspects that would escape this tendency, such as religion. 6 Authors 19 evaluated the effect of diversity attributes in the university environment, in interpersonal relationships and in the academic performance of a private superior teaching institution. Most of the students consider it important to have common values in education and training, interest in studying, habits and leisure in the students' approach and in the formation of social groups and in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Friends have an important role in the vital cycle of individuals, most of the time, to improve the quality of life. 6 At the university, people with different characteristics, experiences and expectations can unite around a common goal, thus it is natural that there are conflicts of different origins and magnitude. Thus, institutional actions or interpersonal relationship programs can have positive effects to improve interpersonal relationships and self-esteem and reduce depression in students.…”
Section: Introductionmentioning
confidence: 99%
“…Concordando com a literatura empírica (DeSousa & Cerqueira-Santos, 2012;Mendelson & Aboud, 1999;Souza & Hutz, 2008a), a maioria dos participantes possui uma melhor amizade de mesmo sexo. O vínculo concomitante sugere um apego maior a amizades antigas (escola) em mineiros, o que pode ser explicado pela média de idade inferior à dos participantes gaúchos em quase seis anos, posicionando os primeiros no início da adultez-jovem, e os últimos já dessa etapa se despedindo.…”
Section: Discussionunclassified
“…O vínculo concomitante sugere um apego maior a amizades antigas (escola) em mineiros, o que pode ser explicado pela média de idade inferior à dos participantes gaúchos em quase seis anos, posicionando os primeiros no início da adultez-jovem, e os últimos já dessa etapa se despedindo. Nos estudos com amostras gaúcha e sergipana, a origem da amizade mais citada foi, realmente, colega de escola (DeSousa & Cerqueira-Santos, 2012;Souza & Hutz, 2008a).…”
Section: Discussionunclassified
See 1 more Smart Citation